Ocean temperature impact on ice shelf extent in the eastern Antarctic Peninsula - Johan Etourneau (Nature Portfolio, 2019)
Ocean warming contributes to the thinning of the Antarctic ice shelves, however, lack of observations has prevented a quantification of this contribution. Here the authors use geological records to show that 0.3–1.5 °C ocean warming has played a central role on regional ice shelf instability over the last 9000 years.